Should One Perform Hajj Pilgrimages without Paying Zakat? Proposing an Integrating System between Zakat and Hajj - Dodik Siswantoro; Mariati Aprilia Harahap (International Journal of Zakat, 2026)
PurposeThis study aims to examine the legality and mechanism of requiring Hajj pilgrims to pay zakat before performing the Hajj pilgrimage. It seeks to clarify the normative obligation of zakat for financially capable Muslims and to assess the need for a monitoring system prior to Hajj departure. Design/Methodology/ApproachThe study applies a qualitative research method. It collects primary and secondary data from legal documents, scholarly literature, and other relevant sources. The data are analyzed systematically to evaluate the legal basis and institutional mechanism for linking zakat payment with Hajj administration. FindingsThe findings show that many Hajj pilgrims have not fulfilled their zakat obligations before undertaking Hajj. This condition reflects limited awareness and weak institutional monitoring. The study proposes integrating e-zakat digital data with e-SPT and e-Hajj systems to ensure compliance. Through this integration, prospective Hajj and ‘umrah pilgrims can be verified systematically to confirm that they have fulfilled their zakat obligations. Research limitations/implicationsThe study is limited to normative and conceptual analysis without empirical field testing of the proposed integration system. Future research can conduct pilot implementation studies and evaluate the legal, administrative, and technical feasibility of integrating zakat and Hajj databases. Practical implicationsThe proposed system offers a policy framework for religious authorities and zakat institutions to strengthen zakat compliance among prospective Hajj pilgrims. It can improve zakat collection and enhance coordination between zakat management bodies and Hajj administration agencies. Social implicationsThe integration mechanism can increase awareness and discipline in fulfilling zakat obligations. It reinforces the principle that financial capability for Hajj includes compliance with zakat, thereby strengthening social justice and redistribution within the Muslim community. Originality/valueThis study highlights the sequential obligation of zakat before Hajj within the Pillars of Islam and proposes a digital integration model between zakat and Hajj systems. It contributes a new institutional approach to aligning religious obligations with digital governance mechanisms.